2D material based heterostructures for solar light driven photocatalytic H2 production. Issue 8 (7th April 2022) - Wang, Yingying; Ding, Zhu; Arif, Nayab; Jiang, Wei-Chao; Zeng, Yu-Jia
Abstract : Recent advances in 2D material based heterostructures for solar light driven photocatalytic H2 production are summarized. Abstract : Photocatalytic H2 production using solar energy has long been considered as a promising solution for renewable energy production to solve energy crisis and environmental issues. 2D materials with unique layered structures and electronic properties have led to considerable breakthroughs in energy fields. By constructing heterostructures to facilitate solar light absorption and charge transfer and separation, the photocatalytic activity of 2D materials can be highly boosted. In this review, we summarize recent progress in 2D material based heterostructures for solar light driven photocatalytic H2 production, including black phosphorus (BP), g-C3 N4 (CN), transition metal dichalcogenides (TMDs), layered double hydroxides (LDHs), MXenes, and other emerging 2D materials. We provide a fundamental understanding of the functions of various heterojunctions due to their enhanced photocatalytic activity. The band alignments of different heterojunctions with enhanced visible light absorption and improved charge transfer in terms of water splitting reaction are specially discussed. Finally, the existing challenges and prospects of the practical application of 2D material-based heterostructures in photocatalytic H2 production are presented.